An All In Resistivity and Seismic Portable Field System - Almeida, F. E. R. (2017)
A data acquisition system based on LabView virtual instruments was developed to allow both electrical resistivity and seismic wave velocity measurements with no need for switching equipments and standard multicables. This is achieved by simply using eight electrodes as connectors for four geophones when changing from electrical to seismic methods. The Pole Pole resistivity array was adopted using the eight electrodes for potential measurements while the current electrode was manually displaced thus using less cable. The tomographic refraction method was based on four common receiver gathers. Each receiver gather consists of 16 shots one metre apart fired manually This apparatus enables the use of a simple, lightweight and also cheap field system with a good spatial seismic and electrical parameter resolution for multipurpose site characterization. A controlled experiment was done to validate the system